Upon graduation / Priestly Lanting Layang ... [et al.] - Layang, Priestly Lanting; Abang Shamsudin, Dayang Nurul Amieyda; Herman, Nurul Izzah; Standard, Stephanie Sonia; Mokhtar, Muhammad Adib Azfar (Perpustakaan Tun Abdul Razak, 2023)
The university automatically considers you a part of its alumni after you graduate. It merely signifies that you were a student in the past. Although being an alumni doesn't need you to accomplish anything, you can discover that you have access to some unique benefits. Alumni, for instance, could have access to resources or get discounted library membership fees. Discounts for membership with businesses or professional associations are another possibility. Overall, staying connected with your university and its networks is made possible by being an active member of your alumni association. This connection may open up prospects for further education or employment.